Philosophy of biology before biology - Bognon-Küss, Cécilia; Wolfe, Charles T. 1970- (History and philosophy of biology, 2019)
The use of the term "biology" to refer to a unified science of life emerged around 1800 (most prominently by scientists such as Lamarck and Treviranus, although scholarship has indicated its usage at least 30-40 years earlier). The interplay between philosophy and natural science has also accompanied the constitution of biology as a science. Philosophy of Biology Before Biology examines biological and protobiological writings from the mid-eighteenth century to the early nineteenth century (from Buffon to Cuvier; Kant to Oken; and Kielmeyer) with two major sets of questions in mind: What were the distinctive conceptual features of the move toward biology as a science? What were the relations and differences between the "philosophical" focus on the nature of living entities, and the "scientific" focus? This insightful volume produces a fresh but also systematic perspective both on the history of biology as a science and on the early versions of, in the 1960s in a post-positivist context, the philosophy of biology. It will appeal to students and researchers interested in fields such as history of science, philosophy of science and biology